Assessment of network module identification across complex diseases - Choobdar, Sarvenaz; Ahsen, Mehmet Eren; Crawford, Jake; Tomasoni, Mattia; Fang, Tao; Lamparter, David; Lin, Junyuan; Hescott, Benjamin; Hu, Xiaozhe; Mercer, Johnathan; Natoli, Ted; Narayan, Rajiv; et al. (Nature methods, 2019)
In this DREAM challenge, 75 methods for the identification of disease-relevant modules from molecular networks are compared and validated with GWAS data. The authors provide practical guidelines for users and establish benchmarks for network analysis.
Gesehen am 14.04.2020